In silico identification of late blight susceptibility genes in Solanum tuberosum - Sahu, Tanmaya Kumar; Rao, A.R.; Dora, Sasmita; Gupta, Satakshi; Rai, Anil (The Indian Journal of Genetics and Plant Breeding, 2017)
Late blight of potato, caused by Phytophthora infestans, is responsible for high economic loss world-wide. The expression of late blight susceptibility genes (S-genes) in potato cultivars during the infection often favours the pathogenicity. Thus, the identification of the host S-genes, required to enhance susceptibility towards the pathogens under compatible interaction, is highly essential to control the infection. However, to our limited knowledge, fewer late blight S-genes have been identified in potato till date. Therefore, an attempt was made here to identify such genes through a two step classification approach using the primary and derived sequence information of potato proteins. The results revealed that WRKY transcription factor 6, Catalase protein, Shaggy-Like protein kinase NtK-1 and OTU-Like Cysteine protease were found closer to the candidate susceptibility proteins (S-proteins). These proteins were also classified into susceptible category when validated through the computer intensive techniques like Support Vector Machine, Random Forest and Artificial Neural Network. The EST database search for the above proteins has confirmed their expression under the compatible interaction. Besides, the chromosomal locations of the genes encoding these proteins were also identified, so that, the information can be utilized to develop the resistant cultivars. Thus, the predicted S-genes can be used as potential effector targets for late blight resistance in potato.